Application of the five stages of life model to support health impact assessments: a case study of the Llanelli Wellness and Life Science Village. (November 2018) - Reynolds, Richard C; Jones, Craig W; Lloyd, Owain L; Nichols, Caroline D; Davies, Llion
Abstract: Background: Health impact assessments (HIAs) are a requirement for public bodies in Wales following the Public Health (Wales) Act 2017. The Llanelli Wellness and Life Science Village development will co-locate leisure, medical, social, and education services at a former brownfield site in South Wales. We describe the application of the five stages of life model to guide the HIA supporting this development. Methods: The five stages of life model was developed by project stakeholders to align Village services and was also applied to the HIA as a framework. A tri-phase mixed methods approach was used: literature and data review; stakeholder workshop; and public engagement. Many targeted literature reviews were conducted between Dec 8, 2017, and March 13, 2018. For example, the search terms "obesity", "chronic conditions", and "mental health" were entered into Google Scholar (English language restriction). Data on each domain were obtained from sources, such as Stats Wales, and disaggregated to the lowest geographical level. Views were sought at a public engagement event. The stakeholder workshop comprised rotating round-table discussions, with 20 min spent on each life stage. Data were collated and refined via a thematic analysis approach. Findings: The literature and data review identified 102 and 6 sources, respectively, for inclusion. 73 views were obtained from 230 participants. Key recommendations were proposed for each of the five life stages. For early years, village design, promotion of breastfeeding, affordable activities, and collaboration with schools and colleges were highlighted. Welcome outdoor spaces were recommended to maintain a healthy lifestyle via mental health promotion. With respect to chronic conditions, lifestyle interventions, the National Exercise Referral Scheme, and extension of community care (thus reducing hospital use) were proposed. Intergenerational activities and on-site screening were recommended for the frailty cohort. Village inclusivity and accessibility should support end of life care. Interpretation: Applying the five stages of life model to the HIA provided a simple framework that was practical for distributing work between team members, engaging stakeholders, facilitating a timely completion, categorising the vast amount of data, and generating locally relevant recommendations. Funding: None.